1995
DOI: 10.1111/j.2042-7158.1995.tb05736.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Antinociceptive Action of the Hydroalcoholic Extracts from Plants of the Genus, Phyllanthus

Abstract: The analgesic effects of the hydroalcoholic extracts (HEs) of Phyllanthus urinaria, P. tenellus, P. niruri and P. sellowianus have been investigated in several models of nociception in mice.The HE of four species of Phyllanthus (1-90mg kg-l, i.p.) caused a dose-related inhibition of acetic acid-induced abdominal constriction in mice with ID50 values of 5.4, 8.5, 18.2 and 53.0mgkg-I and maximal inhibition (%) of 80 f 2, 67 f 8, 63 f 8 and 50 f 4 for P. urinaria, P. niruri, P. tenellus and P. sellowianus, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 20 publications
1
19
1
1
Order By: Relevance
“…These results clearly demonstrate that the chemical profile of the six Miconia species concerning triterpenes and sterols are very similar. It has been reported that a mixture of these compounds is responsible for the biological activities of the extracts they are isolated from (Santos et al, 1995;Gaertner et al, 1999;Otuki et al, 2005). In this context, our data might indicate that the previously reported analgesic effect of the hexane extracts of M. rubiginosa and M. ligustroides in mice could be due to the presence of these compounds.…”
Section: Resultscontrasting
confidence: 54%
“…These results clearly demonstrate that the chemical profile of the six Miconia species concerning triterpenes and sterols are very similar. It has been reported that a mixture of these compounds is responsible for the biological activities of the extracts they are isolated from (Santos et al, 1995;Gaertner et al, 1999;Otuki et al, 2005). In this context, our data might indicate that the previously reported analgesic effect of the hexane extracts of M. rubiginosa and M. ligustroides in mice could be due to the presence of these compounds.…”
Section: Resultscontrasting
confidence: 54%
“…In earlier studies, we have reported that the hydroalcoholic extract obtained from the leaves, stems and roots of Phyllanthus urinaria (Euphorbiaceae), and some related species belonging to this genus, cause dose-related and significant antinociception, mainly when assessed in neurogenic models of nociception (Gorski et al 1993;Santos et al 1994Santos et al , 1995; see for review Calixto et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Of high interest, pain-like crises induced by CYP were consistently prevented by oral treatment with the hydroalcoholic extract from P. niruri. In fact, previous studies revealed marked analgesic effects for this plant extract in several models of nociception in mice (Santos et al 1994;Santos et al 1995;Martini et al 2000). We might suggest that antinociceptive actions of P. niruri extract are mainly related to the presence of compounds quercetin and gallic acid.…”
Section: Discussionmentioning
confidence: 91%